2009
DOI: 10.1186/1745-6215-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of depression and anxiety in adolescents: A randomized controlled trial testing the efficacy and mechanisms of Internet-based self-help problem-solving therapy

Abstract: Background: Even though depression and anxiety are highly prevalent in adolescence, youngsters are not inclined to seek help in regular healthcare. Therapy through the Internet, however, has been found to appeal strongly to young people. The main aim of the present study is to examine the efficacy of preventive Internet-based guided self-help problem-solving therapy with adolescents reporting depressive and anxiety symptoms. A secondary objective is to test potential mediating and moderating variables in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 65 publications
1
29
0
2
Order By: Relevance
“…Some trials have evaluated HIT prevention programs, most with positive benefits (Morgan, Jorm, & Mackinnon, 2012; Lintvedt et al, 2011; Eyrich-Garg, 2010; Christensen et al, 2010a; Hoek, Schuurmans, Koot, & Cuijpers, 2009; Van Voorhees et al, 2009). However, the issue of reach has not been systematically addressed in these trials, but is often inferred as being increased by use of HIT.…”
Section: What Have Previous Studies Shown About Hit Interventions Formentioning
confidence: 99%
“…Some trials have evaluated HIT prevention programs, most with positive benefits (Morgan, Jorm, & Mackinnon, 2012; Lintvedt et al, 2011; Eyrich-Garg, 2010; Christensen et al, 2010a; Hoek, Schuurmans, Koot, & Cuijpers, 2009; Van Voorhees et al, 2009). However, the issue of reach has not been systematically addressed in these trials, but is often inferred as being increased by use of HIT.…”
Section: What Have Previous Studies Shown About Hit Interventions Formentioning
confidence: 99%
“…Examples include Internet-based self-help interventions for symptoms of psychological distress such as depression and anxiety, which have built-in mechanisms to screen for levels of clinical depression and anxiety. 13,14 However, when the collection of remote health data is performed for research and not for clinical purposes, the need to identify potential safety risks is no less serious. Just as remote health monitoring promotes optimal clinical management, because it is possible to immediately recognize changes, remote health monitoring promotes immediate recognition of potential participant safety issues in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of a problem-solving therapy (PST), which currently has no available data, approximately 210 participants between the ages of 12 and 18 with mild to moderate depressive symptoms will be randomized into an active group and a control group 34. This PTS intervention uses a step-by-step approach to first triage problems based on their importance, and then to generate, implement, and evaluate trial solutions.…”
Section: Life Course Schedulementioning
confidence: 99%
“…Also, seven adult studies indicated mostly mid to high levels of education41, 43, 4546, 49, 5354, 64, and most of the youth population was recruited from moderate to high income families33, 35–38, 65. The studies spanned over many regions and to an extent reflected national cultures in Canada49, the United States37–38, 45, 65, Australia33, 3536, 43, and Europe 34, 41, 46, 5254, 64 (mainly the Netherlands34, 41, 46, 5354, 64 and one in Sweden52). However, the degree to which each intervention was tailored to meet the needs of ethnic minorities or cultural differences within each country was not clearly specified.…”
Section: Effective Componentsmentioning
confidence: 99%
See 1 more Smart Citation